2018
DOI: 10.1177/1043454218818067
|View full text |Cite
|
Sign up to set email alerts
|

Siblings’ Experiences of Everyday Life in a Family Where One Child Is Diagnosed With Blood Cancer: A Qualitative Study

Abstract: Background: Childhood cancer not only presents challenges to the life of the child with cancer but also to the siblings' daily family life. The aim of the current study was to gain a better understanding of siblings' experiences of living in a family where one child has been diagnosed with blood cancer. Method: Ten siblings of children with leukemia or non-Hodgkin lymphoma completed a semistructured interview about their everyday family life experiences postdiagnosis. The verbatim transcripts of the interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(89 citation statements)
references
References 45 publications
(84 reference statements)
4
77
0
8
Order By: Relevance
“…In addition, when taking into account the family functioning subscales, there was a significant association between expressiveness and loneliness: the more family members can share their experiences within the family, the less loneliness in all family members. This finding illustrates the importance of family communication (Van Schoors et al, 2018a).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…In addition, when taking into account the family functioning subscales, there was a significant association between expressiveness and loneliness: the more family members can share their experiences within the family, the less loneliness in all family members. This finding illustrates the importance of family communication (Van Schoors et al, 2018a).…”
Section: Discussionsupporting
confidence: 59%
“…When considering the family functioning subscales, a significant association between expressiveness and parental quality of life; and between social orientation and children’s quality of life was found: the more a parent perceived his/her family as expressive and the closer a child is to his/her social environment (e.g., friends), the better his/her quality of life. These findings emphasize the importance of sharing experiences within the family, especially for parents (Van Schoors et al, 2018a) and with the social network, especially for children (McGrath et al, 2005; Beltrao et al, 2007). Furthermore, we found that – for all family members – cancer appraisal was related to quality of life: perceiving the illness as more uncontrollable and less manageable was related to worse quality of life, in parents and in children (patients and siblings).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The present study is part of a larger ongoing study in Flanders (Belgium), examining the impact of a pediatric cancer diagnosis on families (see also Van Schoors et al, 2018, 2019. Using a purposive sampling strategy, children diagnosed with leukemia or non-Hodgkin lymphoma between the age of one and eighteen, their parents and any siblings were invited to take part in a longitudinal survey.…”
Section: Participantsmentioning
confidence: 99%